Comparison between Razor Blade and Depilation Cream for Pre-Operative Hair Removal in relation to Surgical Site Infection - Sah, Chandrika; Pokharel, Nabin; Shrestha, Sunil; Singh, Praveen Kumar; Yadav, Aditya Prakash; Shahi, Sanjiv Kumar (Med Phoenix, 2025)
Introduction: Surgical site infection is one of the significant complications in post-operative patients. Method of preoperative hair removal is also considered as one of the risk factors for causing SSI. Razor blade, depilatory cream, clippers are used for hair removal. The objective of this study is to assess the incidence of SSI with razor blade and depilatory cream.Materials and methods: A comparative study was conducted on 202 patients divided into 101 in each razor blade and depilatory cream group admitted in department of general surgery. Patient aged 15 years and above who required preoperative hair removal was recruited in the study. Patients undergoing surgery for clean and clean contaminated cases were included in the study. Postoperatively, the presence of SSI was evaluated using the Southampton wound grading system.Results: Out of 202 patients, 63(31.2%) patients developed SSI. Among razor group, 41(40.6%) patients and among depilatory group, 22(21.8%) patients had developed SSI. Skin injury was observed in 57(28.2%) of total 202 patients, 51(50.5%) patients in razor and 6(5.9%) patients in depilatory group. Out of 57 patients who had skin injury, 25(43.9%) patients had SSI while 38(26.2%) patients out of 145 patients who had no skin injury developed SSI. Skin reaction was seen in 24 patients, 18(17.8%) patients had depilatory cream and 6(5.9%) patients had razor shaving.Conclusion: Among two methods of preoperative hair removal, depilatory cream found to be superior to razor blade in reducing the incidence of SSI.